SELLING TO BIASED BELIEVERS: STRATEGIES OF ONLINE LOTTERY TICKET VENDORS. (5th March 2015) - Lien, Jaimie W.; Yuan, Jia
<x xml:space="preserve">Abstract</x> We provide evidence that sellers respond to buyers' belief biases in a collective lottery betting market, by adopting sales strategies which cater to believers in the Hot Hand and Gambler's Fallacies. Lottery players on the buyer side tend to avoid buying tickets which are similar to the previous winning ticket, in accordance with the Gambler's Fallacy (Clotfelter and Cook 1993; Terrell 1994). At the same time, buyers tend to prefer purchasing tickets from previously winning sellers, despite the fully random nature of wins, in accordance with Hot‐Hand Fallacy (Croson and Sundali 2005). These behavioral biases provide an opportunity for ticket sellers to increase their expected profits by adjusting features of the lottery portfolios they sell. We find that sellers make changes to their portfolio size, commission rate, self‐purchase rate, and number choices in response to previous events, in ways that are consistent with responding to the Hot‐Hand Fallacy belief, and which also lend a degree of support for responding to the Gambler's Fallacy belief. Our results show evidence of participants in a market accommodating their choices to the biased beliefs of other participants in order to gain an advantage in expected profits. (JEL D01, D03, D81, L86)